Comparative study of drying techniques on the anti-inflammatory content of bitter leaf simplicia (Vernonia amygdalina Del.) - Tamala, Yulianida; Yani, Moh.; Sailah, Illah; Halimatushadyah, Ernie; Tallei, Trina Ekawati (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Bitter leaf (Vernonia amygdalina Del.) hold significant potential for development in the pharmaceutical industry due to its high content of bioactive compounds, particularly flavonoids, which serve as a source of anti-inflammatory agents. A major challenge in processing bitter leaf into dried simplicia is the selection of an appropriate drying technique, as the drying process can alter the active compounds present in the plant. This study aimed to analyze the drying rate of bitter leaf and evaluate the most effective drying technique for preserving their anti-inflammatory properties. The drying process was conducted using an oven dryer at 40°C and 50°C, as well as a greenhouse dryer, and the reduction in moisture content over time was recorded. The dried simplicia was subsequently subjected to phytochemical screening and anti-inflammatory activity testing. The results indicated that the drying durations required to achieve a final moisture content of <10% were 44 hours at 40°C, 20 hours at 50°C, and 9 hours using the greenhouse drying method. Phytochemical analysis confirmed the presence of saponins, alkaloids, flavonoids, tannins, and steroids in the bitter leaf extract. The IC₅₀ values for the three drying methods were determined to be 25.33 ppm, 61.05 ppm, and 114.25 ppm, respectively. Among the drying methods tested, oven drying at 40°C yielded the highest anti-inflammatory activity, with an IC₅₀ value of 25.33 ppm. The regression equation obtained was y = 0.072x + 48.176, with an R² value of 0.9899, indicating a strong correlation between extract concentration and inflammation inhibition. This suggests the potential for reliable prediction of optimal dosages for pharmacological applications.